Impact of opioid dose escalation on the development of substance use disorders, accidents, self‐inflicted injuries, opioid overdoses and alcohol and non‐opioid drug‐related overdoses: a retrospective cohort study. (15th January 2020) - Hayes, Corey J.; Krebs, Erin E.; Hudson, Teresa; Brown, Joshua; Li, Chenghui; Martin, Bradley C.
Abstract: Aim: To understand the potential harmful effects of dose escalation among patients with chronic, non‐cancer pain (CNCP) on chronic opioid therapy. Design: Retrospective cohort study. Setting: United States Veterans Healthcare Administration. Participants: Veterans with CNCP and on chronic opioid therapy were identified using data from fiscal years 2008–15. The Veteran sample was approximately 90% male and 70% white. Measurements: Dose escalators [increase of > 20% average morphine milligram equivalent (MME) daily dose] were compared with dose maintainers (change of ±20% average MME daily dose). A composite measure of subsequent substance use disorders (SUDs: opioid, non‐opioid and alcohol use disorders) and opioid‐related adverse outcomes (AOs: accidents resulting in wounds/injuries, opioid‐related and alcohol and non‐opioid medication‐related accidents and overdoses, self‐inflicted injuries) as well as the individual SUDs and AOs was examined. The primary analyses were conducted among a 1 : 1 matched sample of escalators and maintainers matched on propensity score and index date. Propensity scores were generated using demographic characteristics, medical comorbidities, medication and health‐care utilization characteristics. Subgroup analyses were conducted by quartile of the propensity score. Sensitivity analyses were conducted using adjusted logistic regression, logistic regression using stabilized inverse probability of treatment weighting (SIPTW) and instrumental variable (IV) models using geographic variation in opioid dose escalation as the IV. Findings: There were 32 420 maintainers and 20 767 escalators resulting in 19 358 (93.2%) matched pairs. Composite AOs [odds ratio (OR) = 1.31, 95% confidence interval (CI) = 1.23, 1.40], composite SUDs (OR = 1.31, 95% CI = 1.22, 1.41) and individual SUD and AO subtypes were higher among dose escalators, except for opioid‐related accidents and overdoses and violence‐related injuries. Subgroup analyses within the propensity score quartiles found similar results. Sensitivity analyses with the adjusted and SIPTW logistic regressions found similar results to the primary analyses for all outcomes except for opioid‐related accidents and overdoses, which were found to be significantly higher among escalators. Sensitivity analyses with IV models provided mixed results with SUDs and the individual types of AOs. Conclusion: Escalating the opioid dose for those with chronic, non‐cancer pain is associated with increased risks of substance use disorder and opioid‐related adverse outcomes.